Environmental evaluation of family house materials impacts on climate change, land and water use, acidification and ecotoxicity - Fabianova, Martina; Estokova, Adriana (Frontiers in Environmental Science, 2023)
The construction industry plays a significant role in contributing to various environmental impacts, including climate change, acidification, and ecotoxicity, among others. This research paper presents a scientific analysis focused on the environmental assessment evaluation of a masonry residential house by life cycle assessment (LCA) methodology. Specifically, it investigates the environmental impacts associated with the production phase of materials using the SimaPro software, which employs the Ecoinvent database. The ReCiPe method is utilized to calculate the comprehensive environmental impacts, with particular emphasis on climate change, terrestrial acidification, ecotoxicity, land use, and water use. To accurately determine the environmental impacts of the house materials, an allocation approach is employed, taking into account the function and location of the materials within individual structures. The calculated share of climate change per house materials amounted to 21.59 kg CO2 eq/m 2 /year, while the share on water scarcity was estimated at 15.87 m 3 /m 2 /year. The research findings reveal that vertical structures exhibit the highest environmental impacts across all impact categories, while horizontal structures demonstrate comparatively lower values.